"Quebracho" tannin derivative and boosters biocides for new antifouling formulations - Bellotti, Natalia (2012)
The growth of fouling communities on ships' hulls causes economic losses due to increased fuel consumption and to the deterioration of the metallic substrate by corrosion. Antifouling paints are formulated to avoid the settlement of these organisms and may contain biocides as active compounds. The objective of this research was to evaluate the antifouling performance of paints formulated with a "quebracho" tannin derivative (zinc "tannate") and "boosters" (secondary biocides). The "boosters" used in this study were bismuth lactate, a zeolite exchanged with silver cations, and the same zeolite modified with silver chloride. Bioassays with "boosters" solutions were carried out employing Artemia persimilis. Soluble matrix antifouling paints were formulated and their action was assessed in a natural sea water environment. Results showed that the bismuth lactate resulted in a coating with almost triple service life of the antifouling paints with zinc "tannate." Paints formulated with the silver composites behaved slightly better than the control paint.